KINERJA PERPUSTAKAAN PDII-LIPI SERPONG BERDASARKAN INDEKS KEPUASAN PENGGUNA, RANKING ASPEK LAYANAN, DAN PERBANDINGAN DENGAN LEMBAGA SEJENIS - Yaniasih, Yaniasih; Tupan, Tupan; Yoganingrum, Ambar; Rachmawati, Rulina (BACA: Jurnal Dokumentasi dan Informasi, 2016)
PDII had a unit in Puspiptek Serpong called UPJ PDII Serpong in charge of providing access to scientific information. To improve its service quality, it was necessary to evaluate user’s perception on provided services and compared it to the other library services in Puspiptek area. Evaluation was done on user’s satisfaction in the aspects of content, personnel, facilities, and price. Data were collected using questionnaires in the form of Google Form. Questionnaires were distributed to researchers in Puspiptek Serpong area, which were from LIPI, BATAN, and BPPT. Data obtained were analyzed using statistic descriptive method. Performance aspects were analyzed using Shannon Entropy to get the weight and the rank performances. The Performance of UPJ PDII Serpong compared tothe similar institutions using the Wilcoxon Match Pairs Test. Result showed that the customer satisfaction consist of content availability, servicespeed, price, librarian’s attitude, facilities, suitability of the content had an index of satisfaction with the value of B (Good). The librarian’s attitude had the highest performance, followed by the availability and suitability of content, service speed, facilities, and price. The performance of UPJ PDII Serpong superior in all aspects compared to BPPT and BATAN library performance.